Managing complexity in the public services - Haynes, Philip (London : Routledge, Taylor & Francis Group, 2015)
"Complexity theory has grown in importance over the last decade and its development has enabled a universal method of practice which proposes a pragmatic and humanistic management practice. The application of complexity theory highlights the importance of the development of an organizations culture and communication, it enables them to be dynamic whilst maintaining coherence and stability. It places the workers, their values and mission at the heart of the organizations practices, recognising that information technology may provide a framework for complex communication and knowledge use but cannot replace highly developed professional negotiations and cooperation. This new edition of Managing Complexity in the Public Services argues that the complexity of the public service world limits the usefulness of classical and rational scientific management approaches like the New Public Managerialism (NPM). As a result overly rigid approaches to performance management and strategic management can be highly dysfunctional in the public context. Managing Complexity in the Public Services takes further the articulation of a method of management practice that can cope with the stark realities of the complex and unpredictable public policy world. It develops a number of management practices developed in action research that will be of high use to both academics and practitioners and helps detail how complexity theory can be applied in practice The result is a new value based practice for the post crisis public service world"--
1. Management, professions and the public service context -- 2. What is complexity? -- 3. Strategy and planning in an unstable world -- 4. Complexity and the performance of public services -- 5. Information management -- 6. People in public organizations -- 7. Conclusion.
Includes bibliographical references and index.
Keywords: COMPLEXITY (PHILOSOPHY); PUBLIC ADMINISTRATION